What comes after the two degree target? The EU's climate policy should advocate for flexible benchmarks - Oliver Geden (Stiftung Wissenschaft und Politik (SWP), 2010)
In the climate policy community, there is broad consensus regarding the target of limiting global warming levels to a maximum of two degrees Celsius above pre-industrial levels. Still, barring a breakthrough in UN negotiations in the near future and a reversal in current emissions trends, compliance with the two-degree target will be impossible. If this target is abandoned over the medium-term, the EU would have to make a fundamental strategic decision regarding the structure and stringency levels of a new climate goal. The approach, which has thus far proven dominant, of translating a global temperature cap into precise national emission budgets is hardly feasible from a political viewpoint. Looking ahead, the EU should therefore advocate dynamic formulas for setting targets, which are gauged against benchmarks oriented towards 'climate neutrality
Keywords: 320